A Concept of "Boundary Determination" by the Combination of a Local Flap and Free Tissue Transfer Useful for the Prevention of Postoperative Complications After Complex and Widespread Skull Base Reconstruction. Issue 8 (November 2021) - Tanaka, Kentaro; Sugawara, Takashi; Asakage, Takahiro; Okazaki, Mutsumi
Abstract : Abstract: The transplanted tissue is sutured to the stumps of the bones in skull base reconstruction. Concerning reconstruction by free tissue transfer, it is difficult that the tissue is accurately sutured/fixed to a complex three-dimensional structure. The authors devised a technique in which free tissue transfer is combined with a local flap. A pericranial flap is sutured/fixed onto the irregular border between the cranial and nasal cavities. A free tissue graft is transplanted cranial or caudal to the determined border. Clinical presentation 1 is a patient with carcinoma of the frontal sinus (T4bN0M0). Resection of the frontal bone/nasal bone/medial and superior walls of the orbit, frontal lobectomy was performed. Clinical presentation 2 is a patient with carcinoma of the maxillary sinus (T4aN0M0). Extended total maxillectomy, simultaneous resection of the facial skin/temporal muscle were performed. There were no serious postoperative complications related to compression or occlusion of the cerebral parenchyma or paranasal sinus.